Influence of the growing conditions on the flavonoids and phenolic acids accumulation in amaranth (Amaranthus hypochondriacus L.) leaves. - Barba de la Rosa, Ana Paulina; de León-Rodríguez, Antonio; Laursen, Bente; S. Fomsgaard, Inge (REVISTA TERRA LATINOAMERICANA, 2019)
Phytochemicals or phenolic compounds are important natural bioactive molecules that plants accumulate in response to environmental conditions and may exert benef icial effects on health by protecting humans against many diseases. The aim of this work was to analyze the influence of biotic and abiotic stress on the accumulation of flavonoids and phenolic acids on leaves of two cultivars of Amaranthus hypochondriacus, which are differentiated by the colour of their leaves (red or green). Phenolic compounds were extracted using the accelerated solvent extraction (ASE) method and their identif ication was carried out by LC-MS analysis. Rutin was the main flavonoid in amaranth leaves; the highest concentrations were found in green leaves when plants were subjected to stress (9715 μg g-1). Phenolic acids were minor compounds; ferulic acid was only present in red leaves (0.5 μg g-1) and p-coumaric acid only in green leaves (0.7 μg g-1). Our results indicate that leaves from A. hypochondriacus, the main species that produce edible seeds, are a good source of phytochemical compounds and their accumulation could be driven by the growing conditions.